THE ’STUFF’ OF LIFE: MATERIAL PLAY AND PERFORMANCE IN DIGITAL VIDEO CULTURES AND CONTEMPORARY ART PRACTICE - Nolan, Katherine (AoIR Selected Papers of Internet Research, 2020)
Play and performance with materials and objects can be observed as a trope across digital video cultures. Forms such as slime making tutorials, prank stunts, ASMR and unboxing videos employ different forms of interaction that serve to emphasise material form and sensory qualities. Activities can include pouring viscous glue, crushing tin cans, exploding watermelons, nails tapping on plastic or sinking into sand. Sound, visual and material are employed to create a ‘haptic visuality’ (Marks, 2000) as an affective embodied experience. I will analyse these video cultures as presented in the algorithmic context of YouTube and its claim to user-generated content. Through a DIY culture aesthetic and frame, materials are represented as everyday: the ’stuff’ of life. I will unpack the mimetic representation of ‘reality’ through which these videos function, employing Cowie’s concept of ‘desire for the real’ and Auslander’s discussion of ‘liveness’ in a mediated society (Cowie, 2011; Auslander 1999). I will contextualise this discussion in wider visual culture, drawing parallels with historical and contemporary performance art works. In particular the online practices of David Henry Nobody Jr. and Jan Hakon Erikson, which use play with domestic materials, objects and food to provoke abject, sadistic and absurd voyeuristic pleasures. I will discuss how these works reveal, mobilise, parody and subvert such digital video cultures. In this way, I aim to trace and analyse how this sensory play with material works to ‘hook’ the body of the viewer as a means of harnessing affective labour within the digital economies.